SIDE-TO-END ANASTOMOSIS IN LOW ANTERIOR RECTAL RESECTION - Yu. A. Shelygin; A. S. Budtuev; D. Yu. Pikunov; E. G. Rybakov; O. Yu. Fomenko; S. I. Sevost’Yanov (Вестник хирургии имени И.И. Грекова)
The authors have launched a prospective randomized study aimed to make a comparison of functional results of formation of straight coloanal (control group) and side-to end (main group) anastomosis in case of low anterior rectal resection since 2012. Each group consisted of 40 patients undergoing operation concerning uncomplicated rectal cancer of medium-ampullar section of rectum. It was noted that patients of the main group had lower stool frequency in postoperative period. A function of the interior sphincter was less damaged and the rate of compliance of rectum was high.